Investigation of the Impact of Large-Scale Wind Power and Solar Power Plants on a Vietnamese Transmission Network - Ngo Minh Khoa; Nguyen Thi Hai Van; Le Kim Hung; Doan Anh Tuan (International Journal of Renewable Energy Development, 2022)
Integrating wind power and solar power plants into a power system has significantly grown over the past decade and is expected to grow to unprecedented levels in the coming years. In Vietnam, much large-scale wind power and solar power plants have been built and connected to the power system in recent years. To investigate and evaluate the impact of these power plants on system power operation, the 110kV power transmission network of Binh Dinh province in Vietnam is used in this paper. In the system, the Phuong Mai 3 wind power plant with a capacity of 21MW, the Fujiwara solar power plant with a peak capacity of 50MWp, and the Cat Hiep solar power plant with a peak capacity of 49.5MWp are modeled by using the PSS/E software to simulate and analyze their impacts on power system stability of the 110kV transmission network in Binh Dinh province, Vietnam. Besides, the control strategies of these power plants are also established to investigate their impacts on the network. In addition, this paper proposes three typical scenarios for the wind power and solar power plants in the system. For each scenario, the grid's operating parameters such as voltage variations and frequency variations are acquired for analyzing and evaluating their impacts on the frequency and voltage variations of the network. The simulation results show that the 110kV power transmission network remains in a stable operation mode after the fault scenarios for the wind and solar power plants. Furthermore, these simulation results provide some guidance for the actual operation